2022
DOI: 10.6018/sportk.464401
|View full text |Cite
|
Sign up to set email alerts
|

The role of exercise and physical activity on aging-related diseases and geriatric syndromes

Abstract: Aging is a complex process of physiological and social changes that leads to various diseases. The number of elderly people in the world is increasing dramatically and it should be noted that rapid population aging represents a major public health burden. On the other hand, providing an appropriate and low-cost approach to control and prevent complications such as chronic diseases, physical dysfunction, and the geriatric syndrome is necessary. Also, numerous studies have shown that participation in physical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 42 publications
1
9
0
1
Order By: Relevance
“…Our study results are in line with previous studies that have analysed the association between physical activity and the main types of chronic conditions [ 4 , 8 , 9 , 11 ]. However, we have found significant associations not only in the main types of chronic conditions, like in the systematic review of Bullard et al [ 25 ] but also in other chronic diseases, with a total of 19 chronic conditions in the adjusted analyses.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study results are in line with previous studies that have analysed the association between physical activity and the main types of chronic conditions [ 4 , 8 , 9 , 11 ]. However, we have found significant associations not only in the main types of chronic conditions, like in the systematic review of Bullard et al [ 25 ] but also in other chronic diseases, with a total of 19 chronic conditions in the adjusted analyses.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the objective of this study was to analyse the association between physical activity and the risk of suffering from 32 chronic conditions in a large representative sample of Spanish adults. Considering that previous research has found important benefits of physical activity for health in different populations [ 4 , 10 , 11 ] and that each chronic condition is different, it was hypothesised that low levels of physical activity would be associated with a higher risk of suffering from all chronic conditions, but with a different impact of physical activity on each chronic condition. The results of this study will allow for the design of specific public health strategies and interventions for different chronic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the first stage of the study, an exercise program suitable for older people with diabetes was prepared by a physiotherapist based on national and international guidelines (Izquierdo et al, 2021;Kushkestani et al, 2022;Mañas et al, 2021). At the end of the 6th week, the data collection forms were applied to both groups face-to-face again by the training nurse.…”
Section: The Training Programmentioning
confidence: 99%
“…El proceso de envejecimiento conlleva cambios fisiológicos que repercuten en la vulnerabilidad y desarrollo de enfermedades físicas y mentales, por ello, una mejor condición física se asocia con mejoras en calidad de vida, bienestar y salud mental (Hemmeter & Ngamsri 2022). En la actualidad, la situación demográfica en auge representa una carga para la salud pública (Kushkestani et al 2022). Ante este escenario, se hace necesario comprender las diferentes condiciones que afectan la calidad de vida de las personas mayores y que derivan en una mayor probabilidad de causar deterioro cognitivo.…”
Section: Introductionunclassified